A review of global oyster aquaculture production and consumption. (July 2020) - Botta, Robert; Asche, Frank; Borsum, J. Scott; Camp, Edward V.
Abstract: Oyster farming is one of the oldest forms of aquaculture and oysters are farmed around the globe. As with aquaculture in general, oyster aquaculture production has increased rapidly in recent decades. Despite this, global trends in this production and its markets have received limited attention. This paper presents an overview of global oyster aquaculture production at a country-scale, as well as factors influencing the observed trends. Currently, global oyster aquaculture production is dominated by China, who accounted for 86% of global production by weight in 2016. Beyond China, production is stagnant, and is limited by disease, parasites, and regulatory issues, depending on the country. There appears to be increasing demand for farmed oysters that producers are not able to exploit due to the supply side issues that have limited total production. Additionally, a test for market integration found that there is no global market. Hence, while the increasing prices in some markets provides an opportunity, this is exploited only to a limited extent with Canadian exports to the United States as the best example.